(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Now a day, cloud computing and e-learning is rising speedily and plays a very huge and powerful role in the field of education and learning. Because of this smart phone users can perform their task easily and with effective manner with paying less cost by utilizing the cloud-based applications offered by the cloud service providers. Cloud computing in educational field is going beyond classrooms as an essential service. The higher education, distance education, online education etc. uses the services of cloud computing for the flexibility available for the students. Because e-Learning systems are open, distributed and interconnected, then security becomes an important challenge in order to ensure that interested, and authorised, actors only have access to the right information at the appropriate time. Security issues is one of the biggest concerns that has been affecting the growth of cloud computing. Although there exist some complications with data privacy. This data protection continues to affect the market. Users need to understand the risk of data breaches in the cloud environment. This paper reveals the prevalence of internal cyber-attack as well as a lack of proper IT policies and procedures in e-Learning systems, in light of their standard architecture and their specific security requirements.